La traduttrice si racconta: voci femminili della prima età moderna inglese tra teoria e pratica - Parise, Anastasia; Perrelli, Raffaele; Casagrande, Mirko (Università della Calabria, 2025)
This thesis aims to reconstruct a female theory of translation for the early modern period in Britain and to assess the role of women in the evolution of the history of translation. Five works by Katherine Philips, Aphra Behn, Eliza Haywood, Elizabeth Griffith and Helen Maria Williams are analysed by focusing on the gap between the theory they outline and discuss in the paratexts to their translated texts and their own translation practice. The methodology combines reflexive translation studies, paratextual studies and stylistics so as to answer the following research questions: How do these five women intellectuals represent themselves as translators? Which rhetorical strategies do they employ to do so? How is translation defined from a female perspective? The first chapter explores the historical and cultural context of 17th- and 18th-century Britain with particular attention to the female condition on the one hand and to the main theories on translation on the other. The second chapter outlines a methodological framework in which the analysis of the paratexts (their classification, functions, and stylistic features) is complemented by that of the translations (contrastive analysis of source and target texts). The third and fourth chapters are dedicated to the examination of the paratexts and the translations respectively, while the results are presented in the fifth chapter, where the research questions are finally answered. Only by considering the paratexts and the translations together it is possible to identify the gap between the theory and practice of these five women translators. For different reasons, each of them claims to maintain a stronger adherence to the source text than they actually do. The similarities and differences between the translators’ activity and the stylistic features in the paratextual elements are pointed out in order to outline a female (and possibly proto-feminist) theory of translation in early modern Britain that is characterised by a more or less heavy interventionist approach resulting, in some cases, in the rewriting of their sources. Innovative elements in their linguistic choices and translation practice are identified through a comparison with the prevailing theories of the time. For instance, metaphors based on the rhetoric of modesty and morality are often employed and a domesticating approach is adopted
Dottorato di ricerca in Studi umanistici, Ciclo XXXVII, a.a. 2024-2025